Effect of HUFA in Enriched Artemia on Growth Performance, Biochemical and Fatty Acid Content, and Hepatopancreatic Features of Penaeus vannamei Postlarvae from a Commercial Shrimp Hatchery in Santa Elena, Ecuador - Marina Martínez Soler; Gercende Courtois de Vicose; Javier Roo Filgueira; José Zambrano Sánchez; Edwin Yugcha Oñate; Magaly Montachana Chimborazo; Walter Intriago Díaz; Eduardo Reyes Abad; Juan Manuel Afonso López (Aquaculture Nutrition)
A 12-day experiment was conducted to investigate the effects of Artemia enrichment with two experimental microalgal emulsions (formulated with selected fatty acid contents) on Penaeus vannamei postlarvae. For this purpose, 405,000 postlarvae (stage 1) were obtained from a commercial hatchery in Santa Elena, Ecuador, and distributed into nine fiberglass tanks. Postlarvae were fed for 12 days with three experimental diets (three tanks per treatment): treatment A (Artemia enriched with experimental microalgal emulsion A and dry diet), treatment B (Artemia enriched with experimental microalgal emulsion B and dry diet) and nonenriched Artemia (Artemia without enrichment and dry diet). At the end of the experiment, length (mm), coefficient of variation of population sizes, number of postlarvae in a gram of weight (PL-gram), biochemical composition, fatty acid profile, hepatopancreas perimeter, and histopathological hepatopancreas status of P. vannamei postlarvae (stage 12) were analyzed. To evaluate the status of the hepatopancreas, a categorization range (1–5) was created with different histological parameters such as number of B cells, vesicles around them, healthy tubules, and degradation tissues. Growth traits did not present differences between treatments; total length was 10.17 mm, 10.83 mm, and 10.27 mm for treatment A, treatment B, and nonenriched treatment, respectively, and PL-gram was 141.00, 162.00, and 142.33 for treatment A, treatment B, and nonenriched treatment, respectively. Biochemical composition of postlarvae (lipids, ash, and protein content) did not present differences between the three treatments. Significant differences were observed in the content of three essential fatty acids (DHA, DPA, and ARA) in Penaeus vannamei postlarvae fed with Artemia enriched with experimental emulsions. Thus, DHA content was significantly superior in animals fed with Artemia enriched with treatments A and B (9.80±0.71% and 9.75±0.44%, respectively) than in animals fed with unenriched Artemia (5.78±0.68) (P<0.05). Concerning arachidonic acid (ARA), treatments A and B showed 3.31±0.20% and 3.19±0.09%, respectively, higher than postlarvae fed with unenriched Artemia, 2.73±0.04% (P<0.05). Regarding DPA content, treatments A and B reported higher values of MA and MB (0.81±0.06% and 0.86±0.08%, respectively), than unenriched Artemia (0.43±0.02%) (P<0.05). Interestingly, the increase in DHA, DPA, and ARA contents in postlarvae coincided with the increase in hepatopancreas perimeter. In addition, a large number of B cells, a large number of healthy tubules, increased dilatation of the central tube, and a lower percentage of deteriorated tissue were observed in the hepatopancreas when postlarvae were fed with enriched Artemia.